Sound level study of a hybrid car. Issue 1 (December 2020) - Staneva, G; Dimitrova, K; Ivanov, R; Kadikyanov, G
Abstract: One of the main reasons for the urban noise are the cars. When the hybrid cars are moved in low-speed mode, reduced noise is supposed. In the presented paper have been made comparative analysis according to standard methods of the external and internal sound levels of a hybrid car. The experiment at different speeds in two modes – using ICE and using electric traction were carried out. The results of the measurements are visualized in graphs and tables. They show variation of external and internal sound levels at different speeds in separate octave bands. Spectral analysis at each speed is done. The results show changing of sound level vs speed and noise predominant maximums at respective frequencies.